Contributions of Marx and Gramsci thought to school education (Research, Society and Development, 2020)
This theoretical study presents an analysis of the education proposal in the works of Karl Marx and Antonio Gramsci. From the woven readings, we understand in the Marxian ideal a pedagogy engaged in the transformation of current society and linked to the interests of the working class, being visible the proposal of human emancipation through the educational. Gramsci presents the unitary school proposal with humanist and revolutionary ideals.